Determinan Merek, Kualitas Produk, dan Word Of Mouth Pada Keputusan Customer Membeli Produk Rabbani di Kota Jambi - Rafidah Rafidah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2018)
Halal industry is growing with hijrah tren in Indonesia, one of its products is veil or hijab. In Jambi city it has born many shops with varian brands, such as Zoya, Pashima, and Rabbani. This paper aims to determine the effect of the Merk, Word of Mouth and Products Quality toward consumer decision to buy Rabbani’s Product in Jambi city. The type of research is explanatory, data were collected using interviews questionnaires, cluster sampling technique with the amount of samples 100. Data were analyzed through validity test, reliability test, correlation coefficient, determination coefficient, multiple linear regression, t test and F test data were analyzed quantitatively using SPSS. The result shows that merk, product quality and word of mouth are significantly affected to customer decision to buy product in Rabbani Jambi